2019
DOI: 10.1186/s13100-019-0151-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of transposable element activity on therapeutically relevant human stem cells

Abstract: Human stem cells harbor significant potential for basic and clinical translational research as well as regenerative medicine. Currently ~ 3000 adult and ~ 30 pluripotent stem cell-based, interventional clinical trials are ongoing worldwide, and numbers are increasing continuously. Although stem cells are promising cell sources to treat a wide range of human diseases, there are also concerns regarding potential risks associated with their clinical use, including genomic instability and tumorigenesis concerns. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 292 publications
(367 reference statements)
0
17
0
Order By: Relevance
“…It has been reported that∼124 LINE-1mediated insertions can cause specific genetic diseases (Hancks and Kazazian, 2016), different types of cancer (Babaian and Mager, 2016), and neurodegenerative diseases (Tam et al, 2019). They also adversely affect the prospect of stem cell-based therapies (Schumann et al, 2019).…”
Section: Virus-eukaryote Genetic Exchangementioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that∼124 LINE-1mediated insertions can cause specific genetic diseases (Hancks and Kazazian, 2016), different types of cancer (Babaian and Mager, 2016), and neurodegenerative diseases (Tam et al, 2019). They also adversely affect the prospect of stem cell-based therapies (Schumann et al, 2019).…”
Section: Virus-eukaryote Genetic Exchangementioning
confidence: 99%
“…Human stem cells are indispensable for most basic, clinical, and translational research, such as gene therapy and regenerative medicine. However, they are wider in the clinic and are still limited by their potential risks due to genomic instability and tumorigenesis concerns (Schumann et al, 2019).…”
Section: Tes In Stem Cell-based Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, it is important to understand how TEs contribute to the coding and non-coding transcriptome (You et al 2017;Ma et al 2019;Morillon and Gautheret 2019), if hPSCs are to be used in cell replacement therapy (Fort et al 2014;Schumann et al 2019). However, due to limitations in short-read based sequencing, accurate transcriptome maps have been elusive.…”
Section: Introductionmentioning
confidence: 99%